Ethnotherapeutic Uses and Phytochemical Composition of Physalis peruviana L.: An Overview - Kasali, F´elicien Mushagalusa; Tusiimire, Jonans; Kadima, Justin Ntokamunda; Tolo, Casim Umba; Weisheit, Anke; Agaba, Amon Ganafa (The Scientific World Journal, 2021)
Background: Plant-derived medicines are widespread and continue to increase in traditional and modern medicine, especially in developing countries. Physalis peruviana L. is among the most used plants in conventional medication worldwide. +is review aimed to highlight the ethnotherapeutic uses and phytochemical status of identified compounds in P. peruviana. Methods: Data were collected from Google Scholar, PubMed/Medline, SciFinder, Science Direct, Scopus, the Wiley Online Library, Web of Science, and any other helpful search engine using Physalis peruviana as the primary keyword. Results: Some countries, worldwide, use P. peruviana in their traditional medicine system to manage diverse ailments, mainly diseases and gastrointestinal tract disorders (25.33%). Leaf was the mostly used part (49.28%), prepared by decoction (31.58%) and overall administrated orally (53.57%) as the main route of admission. Around 502 phytoconstituents were identified in different plant parts, especially fruit (38.19%) ethanol/ethyl acetate extract. In most cases (36.17%), the solvent of the extract was not specified. Several phytochemical classes were found in the plant, especially terpenes (26.09%) and phenolic compounds (14.94%). Esters were also abundant (11.55%). In the terpenes category, carotenoids were the most abundant (11.15% followed by monoterpenes (8.76%) and diterpenes (3.18%). However, flavonoids (5.17%) followed by cinnamic acid derivatives (3.99%), monophenolic compounds (1.79%), and phenolic acids (1.33M) are the most reported phenolic compounds. Hexadecanoic acid (palmitic acid) was the most cited (five times). Conclusion: P. peruviana plays an essential role in managing diseases in some countries and is rich in chemical compounds, which need to be isolated and investigated pharmacologically before clinical trials.
Keywords: Ethnotherapeutic; Phytochemical; Physalis peruviana